2015
DOI: 10.1155/2015/734703
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Tyrosine Hydroxylase Protein and Apoptosis-Related Genes in Differentiated and Undifferentiated SH-SY5Y Neuroblastoma Cells Treated with MPP+

Abstract: The human neuroblastoma SH-SY5Y cell line has been used as a dopaminergic cell model for Parkinson's disease research. Whether undifferentiated or differentiated SH-SY5Y cells are more suitable remains controversial. This study aims to evaluate the expression of apoptosis-related mRNAs activated by MPP+ and evaluate the differential expression of tyrosine hydroxylase (TH) in undifferentiated and retinoic acid- (RA-) induced differentiated cells. The western blot results showed a gradual decrease in TH in undif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 29 publications
6
41
1
Order By: Relevance
“…Following treatment with RA, there was an increase in the expression of multiple established markers of neuronal differentiation (Table 1 and Supplementary Fig. 3B ), including MAP2 (microtubule-associated protein-2), synaptophysin (present at functional synapses), SatB (a transcriptional factor expressed in cortical neurons), GFAP (a marker of astrocytes), and TH (tyrosine hydroxyolase, a dopaminergic marker) 34 , 35 , as well as corresponding expected decreases in the abundance of vimentin and ID2 genes (Table 1 ) 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Following treatment with RA, there was an increase in the expression of multiple established markers of neuronal differentiation (Table 1 and Supplementary Fig. 3B ), including MAP2 (microtubule-associated protein-2), synaptophysin (present at functional synapses), SatB (a transcriptional factor expressed in cortical neurons), GFAP (a marker of astrocytes), and TH (tyrosine hydroxyolase, a dopaminergic marker) 34 , 35 , as well as corresponding expected decreases in the abundance of vimentin and ID2 genes (Table 1 ) 36 .…”
Section: Resultsmentioning
confidence: 99%
“…In the 1980s, MPTP was reported to cause Parkinsonian symptoms (21), and it was later observed that it is biotransformed into toxic MPP + by glial cells, which can cross the blood-brain barrier and enter dopaminergic neurons, resulting in mitochondrial damage, the generation of oxidative stress and the activation of pro-apoptotic pathways (22). In agreement with these previous studies, the present study observed that treatment of SH-SY5Y cells with MPP + induced loss of cell viability, occurrence of apoptotic features, enhancement of caspase-3 activity and cytochrome c, which was associated with the increases in the ratio of Bax/Bcl-2 and the elevation of ROS levels in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…-induced ATF3 and CHOP expression in neuroblastoma cells [9,23]. ATF3 upregulates p53 expression and induces apoptosis in SH-SY5Y cells [23] and other cells [17,36]. Interestingly, a recent study showed that ATF3 upregulation of p53 plays an important role in apoptosis induced by MPP ?…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study showed that ATF3 upregulation of p53 plays an important role in apoptosis induced by MPP ? [36]. CHOP was first identified as a transcription factor that is induced in response to growth arrest and DNA damage.…”
Section: Discussionmentioning
confidence: 99%